Advanced practical approaches to web mining techniques and application - Obaid, Ahmed J. ca. 20./21. Jh; Polkowski, Zdzislaw; Bhushan, Bharat (Advances in web technologies and engineering (AWTE) book series, 2022)
This book brings together all techniques and practical approaches in Web Mining Categories which includes Web Content Mining, Web Structure Mining, and Web Usage Mining, introducing the practical approach of analyzing various web data sources and extracting knowledge by taking into consideration the unique challenges present in the Web Environment.